Kaieteurodicus, description and discussion of a new genus of neotropical aleurodicine whitefly (Hemiptera, Sternorrhyncha, Aleurodicinae) - Martin, Jon H. (Zootaxa, 2008)
Kaieteurodicus gen. nov. is described. It accommodates two new species, K. cereus from Guyana and K. panamensis from Panamá. The new genus is discussed in relation to a study of the genus Aleurodicus Douglas, which is continuing.